KRITIS (CRITICAL INFRASTRUCTURE) AND CURRENT THREATS: CHALLENGES AND OPPORTUNITIES FOR PUBLIC ADMINISTRATION IN MODERN CRISIS MANAGEMENT - Röttinger, Raphael (E-Journal VFU, 2025)
The protection of critical infrastructure (KRITIS) has become a key responsibility of public administration, particularly in the context of large-scale events such as football matches. Ensuring security in these settings is not only a question of law enforcement but also a complex administrative challenge that requires strategic coordination, crisis preparedness, and innovative solutions. Rising threats, including stadium violence, terrorism, and evolving security risks, necessitate an adaptive and forward-thinking approach from authorities. This paper explores the role of public administration in safeguarding critical infrastructure, with a particular focus on football stadiums as high-risk venues. By examining contemporary threat scenarios, institutional security strategies, and the integration of emerging technologies, this study highlights how government agencies manage both preventive and reactive measures. The discussion also considers the ethical and legal implications of security policies, as well as the importance of cross-sector collaboration between law enforcement, sports organizations, and technological partners. The findings emphasize that effective crisis management in public administration extends beyond traditional policing efforts. It requires a holistic strategy that combines regulatory frameworks, advanced surveillance technologies, and community engagement to build resilience and mitigate risks. In an era of increasing security concerns, fostering adaptable and socially responsible approaches is essential to maintaining the safety and functionality of critical infrastructure.